(untitled) (Journal of Economic Research & Business Administration, 2015)
To identify the risks arising from the articles of innovative projects and provides their management. Innovative service innovation to reduce the uncertainty of innovation in risk management is to increase the benefits from the introduction of innovative measures to reduce the costs of achieving these goals . Compared with the traditional business risk and other high-risk innovative entrepreneurship . Therefore, special attention should be paid to risk management in the pursuit of innovation .